The impact of fiscal deficit on inflation in Namibia - Joel Hinaunye Eita; Victoria Manuel; Erwin Naimhwaka; Florette Nakusera (Journal of Central Banking Theory and Practice, 2021)
This paper examined the impact of fiscal deficit on inflation in Namibia. The paper employed Autoregressive Distributed Lag Model (ARDL) and Granger causality approach using quarterly data for the period 2002 - 2017. Empirical results showed evidence of a long run positive effect of fiscal deficit on inflation in Namibia. This suggests that fiscal deficit has a direct effect on inflation in Namibia. The study also found a unidirectional causality running from fiscal deficit to inflation in Namibia. The study confirmed that South Africa's prices have positive effect on inflation in Namibia. The key policy implication drawn for the result is that if not contained, high negative fiscal balances could impair the monetary policy objective of price stability. It is therefore advised that fiscal and monetary policies need to be well coordinated to bring fiscal deficit within acceptable level. Given that the main monetary policy goal in Namibia is to achieve and maintain price stability, the results in this study suggest that monitoring budget deficits and price developments in South Africa to develop informed policies is one way to achieve this objective.
Keywords: C2; C3; E310; H72; 330; fiscal deficit; inflation; Namibia; ARDL; cointegration; Haushaltsdefizit; Inflation; Namibia